Judean Desert Refugees as Economic Actors: Agency and Memory from the Ketef Jericho Archives - Nam, Roger S. (Dead Sea discoveries, 2026)
This paper analyzes the Ketef Jericho archives, deposited during two distinct periods by refugees fleeing Ptolemaic expansion in the late 4th century BCE and Roman violence in the early 2nd century CE. Drawing on frameworks of agency and memory from refugee studies, it explores how displaced Judeans continued to function as economic actors, curating administrative documents amid upheaval. The texts and accompanying material culture reflect not only integration into broader economic systems but also a deliberate preservation of memory and an optimistic expectation of return. Yet this optimism was eclipsed by calamity, as archaeological evidence suggests these individuals perished in hiding. This study reframes refugee life in the Judean desert not as marginal or reactive, but as a space of archival continuity and economic participation—a dynamic, if ultimately tragic, exercise of resilience.